Effect of selected determinants on the sustainability of SMEs: Does gender matter? - Jan Dvorsky; Katarina Frajtova-Michalikova; Katarina Zvarikova (Administrative Sciences, 2024)
The paper aims to find disparities in the perception of sustainability-related criteria's impact on the sustainability of the SMEs in the countries of the V4 based on gender. The case study was conducted on 1398 responses from owners or top managers in Visegrad Group countries (V4). The questionnaire contained 52 questions. Data collection was conducted by an external agency using the CAWI methodology. The statistical hypotheses were verified by applying structural equation modelling (SEM method). The empirical findings are important for many authors and researchers. The environmental aspect of entrepreneurship is the most important factor, having a strong positive impact on the sustainability of SMEs. This includes active involvement in environmental protection, environmental responsibility as a part of SME governance, and the perception of owners regarding the environment in firm management. Gender disparities are important in evaluating financial management, the level of digitalisation in a firm, human resource management, and business ethics, and their effect on the sustainability of SMEs.
Keywords: 350; empirical research; effect; SMEs; sustainability; V4 countries